The costs of excess medical claims for automobile personal injuries - Carroll, Stephen J., 1940-; Abrahamse, Allan F.; Vaiana, Mary E.; Institute for Civil Justice (U.S.); Rand Corporation (Santa Monica, CA : RAND, 1995)
Over the past decade and a half, automobile insurance premiums for personal injury coverage have grown rapidly. Many fear that excess claims for medical care may be a major factor in the increase. This study analyzes the pattern of excess medical claiming across the states to estimate how much excess medical claiming exists and how much it costs consumers. The study concludes that 35-42 percent of claimed medical costs for automobile injuries are excess. In 1993, this excess claiming consumed approximately $4 billion of health care resources, cost insurers $9-$13 billion in compensation for noneconomic losses and other costs, and may have cost consumers $13-$18 billion in auto insurance premiums.
"The Institute for Civil Justice."
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Accident law -- United States; Accidents -- Adjustment of claims -- United States -- Costs; Personal injuries